Extraction of Momordica Charantia assisted by pressurized boiling system / Nazlina Zulbadli - Zulbadli, Nazlina (2013)
Momordica charantia is one edible plant which belongs to Cucurbitaceae family and known for its bitterness. The medicinal properties which include antidiabetic, anthelmintic, abortifacient and antimalarial make this fruit often consumed by people since ancient time. These medicinal effect are due to its phytochemical content that contribute to the properties. There are many types of extraction which include conventional to the new advance techniques to extract Momordica charantia such as boiling or decoction, Soxhlet extraction, pressurized liquid or hot water extraction and supercritical carbon dioxide extraction. In this research, studies were done to identify appropriate operating condition of Momordica charantia using pressurized boiling system. The results showed that the appropriate operating condition regarding yield achieved were sample type (ground), time (one hour), liquid/solid ratio (55:1) and pressure (2.5 bar). Apart from that, the predicted yield value determined by Design Expert software was 3.91% at 90.39 minutes, 44.70 liquid/solid ratio and 2.05 bar. The compounds were identified using Gas Chromatography Mass Spectrometry (GCMS) at five different pressures and results showed that compounds that have medicinal properties were extracted. Medicinal compounds such as gentisic acid, cucurbitacin B, ascorbic acid, /3-sitosterol, and stigmasterol were identified at certain pressure. Comparison with other conventional methods of extraction showed that higher yield of extract was achieved when using pressurized boiling system. Besides, different compounds were also extracted as compared to other extraction methods. Analysis by High Presssure Liquid Chromatography (HPLC) showed that main compound of Momordica charantia which is charantin was optimum at 1.0 bar. From the studies done, it showed that the used of pressurized boiler can help to improve the extraction of Momordica charantia.